2019
DOI: 10.1042/bsr20190537
|View full text |Cite
|
Sign up to set email alerts
|

Young plasma ameliorates aging-related acute brain injury after intracerebral hemorrhage

Abstract: Aging has been shown to contribute to both the declined biofunctions of aging brain and aggravation of acute brain damage, and the former could be reversed by young plasma. These results suggest that young plasma treatment may also reduce the acute brain damage induced by intracerebral hemorrhage (ICH). In the present study, we first found that the administration of young plasma significantly reduced the mortality and neurological deficit score in aging ICH rodents, which might be due to the decreased brain wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 35 publications
2
23
0
Order By: Relevance
“…The results showed that the NDS, mortality rate, BWC of perihematomal brain tissues and levels of inflammatory cytokines, such as IL-6, IL-10 and TNF-α, were lower in old mice than in young mice after ICH ( Supplementary Fig. 1), which was consistent with our previous research [13].…”
Section: Old Mice Have Worse Outcomes Than Young Mice After Ichsupporting
confidence: 91%
See 3 more Smart Citations
“…The results showed that the NDS, mortality rate, BWC of perihematomal brain tissues and levels of inflammatory cytokines, such as IL-6, IL-10 and TNF-α, were lower in old mice than in young mice after ICH ( Supplementary Fig. 1), which was consistent with our previous research [13].…”
Section: Old Mice Have Worse Outcomes Than Young Mice After Ichsupporting
confidence: 91%
“…In the current study, we elucidated the roles and mechanisms of CCL12 in aggravating age-related brain injury after ICH. As reported previously, old mice have worse outcomes than young mice after ICH [13]. Furthermore, we observed that the brain and plasma CCL12 levels were markedly upregulated in old mice compared with young mice regardless of ICH, and circulating CCL12 was demonstrated to enter the brain, where it initiated proinflammatory responses.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The ICH model was conducted according to our previously developed method (Yuan et al, 2019). Briefly, mice were immobilized on the stereotaxic apparatus (RWD Life Science Co, Shenzhen, China) after being anesthetized with 3% isoflurane for induction and 1.5% for maintenance.…”
Section: Ich Modelmentioning
confidence: 99%